2021
DOI: 10.1136/bmjsem-2020-000924
|View full text |Cite
|
Sign up to set email alerts
|

Exploring activity levels in physical education lessons in the UK: a cross-sectional examination of activity types and fitness levels

Abstract: ObjectivesTo establish pupil fitness levels, and the relationship to global norms and physical education (PE) enjoyment. To measure and describe physical activity (PA) levels during secondary school PE lessons, in the context of recommended levels, and how levels vary with activity and lesson type.MethodsA cross-sectional design; 10 697 pupils aged 12.5 (SD 0.30) years; pupils who completed a multistage fitness test and wore accelerometers to measure PA during PE lessons. Multilevel models estimated fitness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Likewise, the HELENA study that measured the level of physical activity and time spent in a sedentary manner in adolescents from nine European countries observed, as in this research, that those who carried out moderate-to-vigorous-intensity activity had high cardiorespiratory fitness and spent less time on sedentary activities, but most adolescents spent most of their time displaying sedentary behavior [ 33 ]. It appears that the relative decline of this moderate-to-intense activity affects both sexes from an early age [ 34 ], decreases over the years [ 30 , 35 ] and is greater in girls [ 30 , 33 , 34 , 35 , 36 ]. The adequate physical activity level of our study is a good result due to the well-known role of physical activity to prevent premature mortality [ 37 ], improve cardiometabolic health [ 38 , 39 , 40 , 41 , 42 ] and aerobic capacity and muscular force [ 8 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the HELENA study that measured the level of physical activity and time spent in a sedentary manner in adolescents from nine European countries observed, as in this research, that those who carried out moderate-to-vigorous-intensity activity had high cardiorespiratory fitness and spent less time on sedentary activities, but most adolescents spent most of their time displaying sedentary behavior [ 33 ]. It appears that the relative decline of this moderate-to-intense activity affects both sexes from an early age [ 34 ], decreases over the years [ 30 , 35 ] and is greater in girls [ 30 , 33 , 34 , 35 , 36 ]. The adequate physical activity level of our study is a good result due to the well-known role of physical activity to prevent premature mortality [ 37 ], improve cardiometabolic health [ 38 , 39 , 40 , 41 , 42 ] and aerobic capacity and muscular force [ 8 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our study was not designed to test the impact of PE lessons on HRF directly, it seems empirically unlikely that there would be no detrimental effects of declining exposure to PE, given the well-known benefits of exercise. These reductions in HRF measures may have been further exacerbated by a change in the type of PE lessons provided 43. Evidence from the Fit to Study project indicated that very few students are performing any significant degree of PA within the PE lesson and the majority of lessons taught are ones in which the lowest levels of PA and exercise intensity are recorded 43.…”
Section: Discussionmentioning
confidence: 99%
“…These reductions in HRF measures may have been further exacerbated by a change in the type of PE lessons provided 43. Evidence from the Fit to Study project indicated that very few students are performing any significant degree of PA within the PE lesson and the majority of lessons taught are ones in which the lowest levels of PA and exercise intensity are recorded 43. This should lead to further research exploring, which PE lessons produce the highest amount of PA while allowing the students to learn the required fundamental movement skills.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching Games for Understanding enhances the intensity of PA in the class and reduces sedentary time compared to a hybrid TGfU-SE. This issue is particularly important since increasing PA levels in PE classes is a priority strategy for achieving PA for health guidelines [ 39 , 40 ]. On the other hand, a recent systematic review and meta-analysis of moderate-to-vigorous PA levels in secondary school PE lessons [ 41 ] underlines the importance of looking for new research and intervention strategies to increase classroom activity time.…”
Section: Discussionmentioning
confidence: 99%